A field experiment reveals seasonal variation in the Daphnia gut microbiome. Issue 12 (24th October 2021) - Hegg, Alexander; Radersma, Reinder; Uller, Tobias
Abstract : The gut microbiome is increasingly recognized for its impact on host fitness, but it remains poorly understood how naturally variable environments influence gut microbiome diversity and composition. We studied changes in the gut microbiome of ten genotypes of water fleas Daphnia magna in submerged mesocosm enclosures in a eutrophic lake over a period of 16 weeks, from early summer to autumn. The microbial diversity increased when Daphnia were reintroduced from the laboratory to the lake, and the composition of gut microbes drastically changed. Both gut microbiome diversity and composition continued to change over the 16‐week period, with alpha diversity peaking in late summer. The gut microbiome community was clearly distinct from that of the surrounding water, and temporal changes in the two communities were independent of each other. There were no consistent differences in the gut microbiomes among Daphnia genotypes in the lake environment. The change in gut microbiome over the season was accompanied by a decline in reproductive output and survival. There were weak, but statistically supported, effects of microbiota composition on Daphnia fitness, but there was no evidence that natural variation in microbiome diversity or composition was associated with tolerance to the cyanotoxin microcystin. We conclude that the gut microbiome of Daphnia is highly dynamic in a natural lake environment, but that host genetic effects on microbiome diversity and composition between genotypes within a population can be vanishingly small. These results emphasize that establishing the ecological effects of gut microbiota will require large‐scale experiments under natural conditions.